The Effect of Using Pencak Silat Front Kick Precision Modifications on The Level of Confidence in SMP Negeri 2 Surabaya - Auliya Sari; Nanang Indriarsa (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
Pencak silat is a subject that is rarely carried out in schools, because of the lack of educators who know about pencak silat and pencak silat is a sport that is quite dangerous so if it is carried out in schools there must be strict guard against students and interesting innovations in implementation of pencak silat learning. This study aims to determine the influence and how much influence the use of modified pencak silat front kick accuracy aids on students' confidence levels. This study used a quantitative descriptive approach with the PreExperimental method, Design One Group Pretest-posttest. The instrument used in the study was the Self-Confidence Questionnaire consisting of 40 indicators. This research was conducted in class VII-J which amounted to 30 students. The results of an increase in the Self-Confidence Questionnaire by 74.43% in the high category. The conclusion of the influence of student confidence in pencak silat learning using modifications to the pencak silat front kick determination tool can be seen from the results of the pre-posttest with calculation results of an increase after the provision of pencak silat learning using front kick aids with the results of an increase in self-confidence questionnaire of 67.00.